Response of Ervatamia coronaria to plant growth regulators and chemical fertilization - Ashour, Hossam Ahmed; Mohamed, Eman Zaki Othman; El-Attar, Asmaa Badr El-din Sayed (Ornamental Horticulture, 2023)
The present experiment was conducted to determine the effect chemical fertilization rates and foliar application of plant growth regulators PGRs (Kinetin or Napthaleneacetic Acid (NAA) and their interactions on growth, flowering, chemical composition of Ervatamia coronaria plants. The plants were fertilized monthly with NPK at the rate of 2, 4 and 6 g pot-1, in addition to the control plants. Plants received the fertilization treatments were sprayed monthly with either Kinetin or NAA at 50, 100 ppm for each one, while the control plants sprayed with tap water. As general, the results indicated that within each level of fertilizer treat- ments, treating plants with different concentrations of PGRs (Kinetin or NAA) resulted in significant increase in tested vegetative growth (in terms of plant height, number of branches plant-1, leaf area, number of leaves plant-1, stem diameter, root length, fresh and dry weights of leaves, stems and roots), flowering parameters (Viz number of flowers/ plant, fresh and dry weights of flowers), chlorophylls content, total carbohydrates, N, P , K%, total indoles and total phenols, gibberellins, auxins and cytokinins compared to control, with superiority of NAA particularly the highest concentrations (100 ppm) . Under the same level of PGRs raising the fertilization rate caused a gradual and significant increase in all tested parameters compared to control. Based on the results, it can be recommended that for the highest quality growth and flowering parameters of Ervatamia coronaria, the plants could be sprayed with NAA at 100 ppm combined with 6 g pot-1 NPK.